Topofilia : razones del retorno de mujeres y familias campesinas (2017)
ABSTRACT: The armed confrontation experienced in the Eastern Region of Antioquia (Colombia), provoked a series of transformations in the lifestyles and the social relations of their inhabitants, who despite the act of displacement, decide to retake their territories, on their own initiative, with or without the assistance of the State, to rebuild their project of life. This is how the country people return to their lands moved by the economic precariousness, which they experience in the place where they live as displaced people, but also as a result of strong feelings of attachment to the place and the environment that they used to inhabit. A concept, which frames these feelings of attachment is that of Topophilia, which comprises the affective links of the human being with his environment. Nevertheless, men and women make sense of their environment differently. They give it different meanings depending on the roles that they play in society and according to the marked roles of gender, which influence on the manners that they use to perceive the environment, their attachment to it, as well as the implications that those roles have on the social construction of the territory.